A tarifação do dano extrapatrimonial nas relações de trabalho sob o prisma da Constituição de 1988: análise crítica da Lei 13.467/2017 - Nunes, Cicília Araújo (2020)
This paper aims to analyze a legislative change promoted by the labor reform (Law 13.467/2017) in relation to personal damages related to labor relations (art. 223-G, §1º, CLT). The methodology used was legal hermeneutics, with the aim of to interpret the art. 223-G, §1º, CLT, in the context of the brazilian legal system. The Law 13.467/2017 aligns with neoliberal ideals, a model that currently predominates in the global scenario, including in Brazil. Neoliberalism advocates the flexibilization and deregulation of working conditions as a way to benefit predatory capitalism by removing labor rights to increase profits in the business sector. The charging of personal damages directly violates the principle of human dignity by pricing the dignity of the worker, disregards the constitutional command of guaranteeing ample compensation for personal damages (art. 5, V and X, CF/88), violates the constitutional principle of equality, as well disregards the principle of prohibiting social regression. The art. 223-G, §1º, of the CLT, is not in line with the axiological matrix of the Federal Constitution, based on the valorization of the human being and guarantor of decent work.